Application of electromagnetic sensor in electro-pneumatic actuator displacement control under variable loads conditions: experimental analysis - Sunar, Noorhazirah; Rahmat, Mohd Fuaad; MohdFaudzi, Ahmad ‘Athif; Ismail, Zool Hilmi; Othman, Siti Marhainis; Sulaiman, Siti Fatimah; Abd Wahab, Nur Haliza (Malaysian Society for Computed Tomography & Imaging Technology (MyCT), 2021)
Dead-acme is a major issue that ( degrades (he performance of the positioning control system in the pneumatic proportional valve control system. In order to address the issue, a switching inverse dead-zone compensator was incorporated to the pole-placement control of the Electro-Pneumatic Actuator (EPA) systems driven by a proportional directional control valve, The focus of this study is to do an experimental analysis to evaluate the robustness of the system under varying loads and varying position distances. Electromagnetic sensor is used to measure the displacement of the pneumatic cylinder piston movement, I n this paper, the EPA model was chosen as a Hammerstein model that contains an Autoregressive with exogenous tent (ARX) model and a nonlinear dead-zone model, The ARX mode] is estimated using the Recursive Least Square (RLS) method and the nonlinear model is obtained by using the Particle Swarm Optimization {PSO) method, The position tracking of the EPA system adapts to the pole-placement control law and is combined with switching inverse dead-zone in a feedforward manner. Experimental investigations were earned out for varying loads from 3.1 kg to 23-5 kg and varying position distances from 25 mm to 200 mm. Experimental results show that the EPA system controlled by the proposed controller is able lo perform no overshoots For loads weighing less than 23.5 kg for all tested position distances. Jn addition, the proposed method achieved a steady state position error of 0.4(5 mm, a rise time of 0.21 s and a settling time of 0.49 s. The results demonstrated that as the load weight and position distance increased,transient time increased. However, the proposed method has successfully controlled the positioning of the EPA systems for all tested load weight and position distance.